Timing and Extent of Inbreeding in African Goats - Nandolo, Wilson; Mészáros, Gábor; Banda, Liveness Jessica; Gondwe, Timothy N.; Lamuno, Doreen; Mulindwa, Henry Aaron; Nakimbugwe, Helen N.; Wurzinger, Maria; Utsunomiya, Yuri T.; Woodward-Greene, M. Jennifer; Liu, Mei; Liu, George; et al. (Frontiers in Genetics, 2019)
Genetic characterization of African goats is one of the current priorities in the improvement of goats in the continent. This study contributes to the characterization effort by determining the levels and number of generations to common ancestors (“age”) associated with inbreeding in African goat breeds and identifies regions that contain copy number variation mistyped as being homozygous. Illumina 50k single nucleotide polymorphism (SNP) genotype data for 608 goats from 31 breeds were used to compute the level and age of inbreeding at both local (marker) and global levels (FG) using a model-based approach based on a hidden Markov model (HMM). Runs of homozygosity (ROH) segments detected using the Viterbi algorithm led to ROH-based inbreeding coefficients for all ROH (FROH) and for ROH longer than 2 Mb (FROH>2Mb). Some of the genomic regions identified as having ROH are likely to be hemizygous regions (copy number deletions) mistyped as homozygous regions. Although the proportion of these miscalled ROH is small and does not substantially affect estimates of levels of inbreeding for individual animals, the inbreeding metrics were adjusted by removing these regions from the ROH. All the inbreeding metrics varied widely across breeds, with overall means of 0.0408, 0.0370, and 0.0691 and medians of 0.0125, 0.0098, and 0.0366 for FROH, FROH>2Mb and FG, respectively. Several breeds (including Menabe and Sofia from Madagascar) had high proportions of recent inbreeding, while Small East African, Ethiopian, and most of the West African breeds (including West African Dwarf) had more ancient inbreeding.